The Legitimacy of Authentic Deeds Read by a Notary via Teleconference - DHARSANA, I Made Pria; SUJANA, I Nyoman; MADE FERRARI , John (Indonesia Strategic Sustainability, 2023)
Purpose:A notary is a public official who must provide services to the community; it is desired to be included in responding to the progress of the times, especially those related to the use of technology through teleconferences. Teleconference is a human association or association that is carried out at a far radius using electronic means.Methodology:The type of research used is normative legal research. The object under study is legal norms, namely related to norms contained in article 16 paragraph (1) letter (m) UUJN-P confirms that a notary must be physically present and sign the deed in the presence of appearers and witnesses. In fact, with technological advances that are very supportive, appearers and witnesses may not be physically present, for example, by holding a teleconference.Findings:The results of this study are that the formality of an authentic deed read by a Notary via teleconference media via video is valid and must have completed parameters related to evidence so that the norm of proof is explained, namely that a proof given at trial is valid as evidence, fulfilling all formal and material aspects.Implication:Regarding the deed that is permitted to use video conferencing media in the form of a general meeting of shareholders (GMS), where the parties are not required to be present at the preparation of the deed, it is enough to be replaced by someone to come to the notary. The signing of the deed in this era of digitalization has yet to have full proof.